Public perceptions of stakeholder influence on Australian metropolitan and local plans. Issue 2 (3rd April 2019) - Ruming, Kristian
ABSTRACT: Public participation and engagement is a central element of the Australian planning system at both the metropolitan and local scales. However, despite academic and practitioner debates around the best time for and method of engagement, there is a lack of research which examines the wider public perceptions of the planning system. It is these wider perceptions which set the context for public participation. The particular focus of this paper is on public perceptions about the influence of various interest groups on what is incorporated into metropolitan and local plans. The perceived influenced of four stakeholder groups is examined: individual developers; developer lobby groups; resident opponents; and, residents (general public). The research reveals that a large proportion of the public is critical of the influence of private sector actors and resident opponents, and cynical over the level of influence residents have on planning documents. These perceptions emerge as significant barriers to public engagement, no matter what the method or theoretical foundation.